L’Aquila, smart city medievale. Ossimori resilienti e intime allegorie di una ricostruzione post-sisma - Ciccaglione, Rita (Antropologia Pubblica, 2024)
In the public debate, catastrophe is a destructive and crisis-maker event; complementarily, the culture of resilience turns the disaster into a window of possibility for building a better future. Also in L’Aquila, some strategies for resilience are moved in the post-earthquake by an international expertise team, whose mission is to offer a proposal and a plan of change and transformation to the town. A natural analogy between urban resilience and smartness and its plurality of contents create the conditions to develop a kaleidoscopic imagine of the city by placing the emphasis on one aspect rather than on another. Urban regimes overlap generating oxymoric representations and guiding principles and spatializing growth recipes and models in the downtown or in the polycentric territory. The smart approach becomes synonymous with a (technologic) innovation to be expanded to the internal areas and the medieval city focuses on historic and cultural heritage localized in the old town and rebuilt where it was and how it was. By materializing in the urban space prototypes of figurability, the recovery process can be represented as a change that looks to the future or as a continuity with the past. Intimate ways of representation ascribe to the smart or to the medieval city some allegoric meanings that describe the changement or the endurance of a local social organization based on real estate property.